Ethical implications of the use of artificial intelligence in higher education - Camacho Vázquez, Martha Ruth; Pérez Méndez, Jazmín; Cárdenas Castellanos, Janitzín; Adaile Benítez, Nadia Teresa (Emerging Trends in Education, 2025)
The implementation of Artificial Intelligence (AI) in higher education poses significant ethical dilemmas that require a deep understanding to ensure its beneficial and equitable use. This research explored the ethical challenges associated with the use of AI, specifically ChatGPT, in the university setting. The methodology was developed in two phases: a systematic literature review and field research using surveys of university students. The results revealed a generally positive attitude toward ChatGPT, with strong recognition of its usefulness and the importance of AI literacy. However, concerns about academic integrity and the potential promotion of mental laziness were identified. A weak correlation was found between major choice and ethical perceptions, while age showed no significant influence. The study also highlighted the need to improve citation and source verification practices when using AI. These findings provide a solid foundation for the development of institutional policies and educational programs that address the ethical challenges of AI in higher education, emphasizing the importance of tailored approaches according to academic discipline.
Keywords: Ethics; Artificial Intelligence; Higher Education; University; Learning